Advances in Lifespan Psychology: A Focus on Biocultural and Personal Influences. - Shu-Chen Li; Freund, Alexandra M. (Research in Human Development, 2005)
A central task of lifespan psychology is to understand the interactive and dynamic nature of contextual and individual influences on development. Guided by this research orientation, recent lifespan research has addressed coconstructive mechanisms that involve reciprocal interactions between biology and culture at the contextual level as well as interactions between personal goals and developmental resources at the individual level. This review selectively focuses on such recent theoretical and empirical developments in understanding (a) the relative contributions of biology and culture across the lifespan, (b) biocultural coconstruction of developmental plasticity, and (c) the individual's regulatory processes (selection, optimization, and compensation) operating in the interactions between personal goals and developmental resources.